Tumor necrosis factor gene polymorphism rs1800629 in patients with atherosclerotic cardiovascular diseases: A review - Elena V. Khazova; Olga V. Bulashova; Elena V. Valeeva (ZAO "Consilium Medicum", 2023)
The close attention of researchers is riveted to the study of socially significant multifactorial diseases and syndromes with a hereditary predisposition, which include chronic heart failure, formed as a result of atherosclerosis of the coronary arteries. The promise of genomic studies in atherosclerosis and heart failure is associated with the possibility of determining the genetic risk of developing and predicting adverse cardiovascular events before the onset of clinical signs/symptoms. From the standpoint of understanding the pathogenesis of atherosclerosis as a variant of nonspecific inflammation, which has a wave-like character, it is assumed that genes encoding pro-inflammatory cytokines influence the pathological process. The aim of the review was to analyze the results of studies available in available publications on the rs1800629 polymorphism of the tumor necrosis factor (TNF) gene in patients with atherosclerotic cardiovascular diseases. Most data indicate the presence of an increased cardiovascular risk in carriers of the A allele of the rs1800629 polymorphism of the TNF gene. It was determined that carriage of the AA genotype is associated with essential arterial hypertension and remodeling of the left ventricular myocardium. In patients with chronic heart failure with preserved and moderately reduced left ventricular ejection fraction of the AA genotype, low blood pressure and frequent occurrence of atrial fibrillation were noted. A number of papers present the results of studies of the rs1800629 polymorphism of the TNF gene and the prognostic significance of the rs1800629 polymorphism of the TNF gene in heart failure.